KAJIAN LAPANGAN MENINGKATKAN KEMAHIRAN PEDAGOGI GURU SEJARAH: STUDI KASUS DI TAPAK ARKEOLOGI LEMBAH BUJANG DAN SUNGAI BATU - Punitha Muniandy; Nagamah Marimuthu; Abdul Rahim Ali; Sivarajan Ponniah; Zahari Zainal; Ravendran Chelliah; Jefriza Jefriza (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2018)
Research was carried upon 40 teachers who teach history at Sekolah Menengah Seberang Prai Tengah, Penang. The purpose of the study is to evaluate the efectiveness of field research in increasing the quality of a History teacher’s pedagogical skills. As many as 40 history teachers of whom 20 were female and the other 20 male from Sekolah Menengah Seberang Prai Tengah were chosen as respondents for the research.The research aspect which was observed is the usage of field research, knowledge or information gained from field research, the feeling of the teacher after carrying out the field research and the effect of the field research programme. The case study at the archeological site of Lembah Bujang and Sungai Batu, Kedah was carried out to observe the significance of the research continuity. A descriptive analysis and a t-test were used. Furthermore, the interview and the observation methods were used upon the research participants to strengthen the research findings. Analysis results indicate the research aspect which is the usage of field research, knowledge or information gained from field research, the feeling of the teacher after carrying out the field research and the effect of the field research programme at the archeological site of Lembah Bujang and Sungai Batu amongst the high school history teachers are not significant, however, the mean score related to the effect of the field research programme at the archeological site of Lembah Bujang and Sungai Batu shows that the male teachers had a much more fun engangement and are more interested in the teaching and learning activities compared to the female teachers.